Overview of Infectious Anemia In chicken and Role of PCR in disease Diagnose - Ayesha Muazzam; Rabia Mehmood (Brilliance: Research of Artificial Intelligence, 2022)
Chicken Infectious Anemia is a viral disease in poultry caused by CAV chicken Anemia virus usually effecting chicken and other species of poultry birds. This review will show the role of PCR which is a device used to diagnose disease. In this review I also brief some sign and symptom of the disease which will help a lay men to diagnose the disease. In this review I also discuss the control method of disease by which we can control the disease and save the farmer from big loss. The objective of that review was to aware the people from risk of CIA and give possible solution to combat with disease. The review will help out scholars to understand CIA. This review also bring light toward the use of PCR as in Pakistan farmer are not using PCR and in result there is big difficulty in diagnose of disease. This study will also aware about use of vaccine to the people so people will know the importance of Vaccine.